2018
DOI: 10.22363/2313-0245-2018-22-3-288-301
|View full text |Cite
|
Sign up to set email alerts
|

Allergen Immunotherapy: Efficacy, Persistence, Consistency, and Cost Effectiveness

Abstract: Although allergen immunotherapy (AIT) has been used for the treatment of allergic rhinitis (AR), allergic conjunctivitis, asthma, stinging insect hypersensitivity, and atopic dermatitis for over 100 years, it has been slow to gain universal acceptance. With the publication of the "World Health Organization Position Paper, Allergen Immunotherapy" in 1998 which summarized the scientific evidence for the efficacy and long-term benefit of this therapy, it has become an accepted and respected modality of treatment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…38 Overall, studies examining the pharmacoeconomics of AIT have been able to demonstrate cost savings. 45 However, if full treatment success is expected with only three continuous seasonal cycles, 27,28 early patient discontinuation considerably impacts the midterm costeffectiveness of AIT, as the investment in year one or even year two without reaching year three could be considered a lost opportunity and non-recoverable cost. The discontinuation rate for SLIT treatments considerably depends on the number of visits to the physician per year.…”
Section: Discussionmentioning
confidence: 99%
“…38 Overall, studies examining the pharmacoeconomics of AIT have been able to demonstrate cost savings. 45 However, if full treatment success is expected with only three continuous seasonal cycles, 27,28 early patient discontinuation considerably impacts the midterm costeffectiveness of AIT, as the investment in year one or even year two without reaching year three could be considered a lost opportunity and non-recoverable cost. The discontinuation rate for SLIT treatments considerably depends on the number of visits to the physician per year.…”
Section: Discussionmentioning
confidence: 99%
“…49 Overall, studies examining the pharmaco-economics of AIT have demonstrated cost savings. 50 Furthermore, Kelly et al showed that corticosteroid-induced growth retardation in prepubertal children persisted even in adulthood, highlighting the need for reducing corticosteroid medication. 51 Our results confirmed the potential of allergoid to reduce the need for asthma medication.…”
Section: Discussionmentioning
confidence: 99%